Gate(s) Keeping or Scot(t) Free? The Legal Environment of Marital Surname Use, Post-Divorce - Gregory R. Bordelon (Columbia Journal of Gender and Law, 2025)
In virtually all states, individuals who adopt their spouse’s surname in marriage do not have clear statutory guidance on the right to use that surname following marital dissolution. Because of the ongoing, pervasive practice of surname-taking in marriage, society has long placed the burden on women, not men, to make a choice upon divorce—one at the core of identity—to decide again on a name. The overwhelming majority of state statutes provide women the option to readopt a surname used before marriage; some even allow the adoption of any new surname. But what if a divorced woman wishes to continue using her marital surname? What if she contributed to the value of that surname during the marriage? What if her personal and social identity came to align with the marital surname? Should she not be able to continue using it on firm legal grounds, beyond mere custom? In a purely legal sense, is the name hers? This Article seeks to establish a firm legal foundation for a divorced individual’s use of their former spouse’s surname following marital dissolution. Part I presents a brief history of surnames, the genesis of hereditary surnames, and the development of patriarchal institutions, such as coverture, that shape a woman’s naming rights. This account includes a history of marital surname usage in the United States, which borrowed from the English common law up to the advent of ostensibly egalitarian protection in a series of 1970s court decisions. Part II examines the social factors driving women to continue using a marital surname and discusses how these matters have shaped the current legal framework of surname usage during a marriage. Part III turns to the law of surname options at the time of divorce and thereafter, detailing the vast differences in the state law governing the area, particularly: what naming options are available in state statutes, when the name change must happen, and who may raise the issue. This section also addresses the legacy of gendered language in these statutes. Part IV proposes a model law on marital surname use post-divorce, establishing guidance and predictability in this area. The model law would allow divorced individuals the statutory ability to confirm their rights in a marital surname for all purposes under a clear, explicit framework.